'When the hurley-burley's done, when the battle's lost and won': exploring the value and appropriation of silence and quietude in academia. Issue 3 (3rd July 2022) - Su, Feng; Wood, Margaret; Alerby, Eva; Da Re, Lorenza; Felisatti, Ettore
ABSTRACT: The intensification of the working life of academics in the corporate world of higher education shaped by new public management, is the backdrop for an exploration of the appropriation of opportunities for silence and quietude through the operation of internalised disciplines of self-imposed control. The paper includes a review of selected literature on the effects of neoliberal education policy reform on the working lives of academics in higher education. Specifically it considers the intensity and pressures and the possibilities for academics to find silence, quietude and respite from the 'hurley-burley', allowing them to 'stand back' from this for a time. The influence of dominant market rationalities in higher education on academic working life is explored, with a particular focus on three national contexts – England, Sweden and Italy. Two vignettes illustrate some of the possibilities and limitations of silence and quietude in academic working life. In the paper, the authors have also examined how the value of such opportunities can be eroded when subjugated for the purposes of the neoliberal academy and the drive for efficiency and performativity.